KINEMATICS AND DYNAMIC EVALUATION OF THE SCREW CONVEYOR OF A CASSAVA CENTRIFUGE DEWATERING MACHINE (Nigerian Journal of Technology, 2014)
This paper presents the volumetric performance of a horizontal enclosed screw conveyor with reference to the influence of vortex motion. Vortex motion is as a result of internal friction, friction between the granular material and surface of the helical blade, and the variable helix angle of the helical flight from the outer periphery of the blade to the shaft. The vortex motion and the degree of fill, govern the volumetric efficiency and the volumetric throughput. An analysis of the vortex motion in a horizontal screw conveyor of a Cassava Centrifuge Dewatering Machine is presented. It is shown that the vortex motion is characterised by the tangential component of the absolute grain velocity being constant with the radial position of a point on the blade. On this basis, an expression for the volumetric efficiency is derived. The volumetric throughput can then be predicted. The study also showed the results of an experimental screw conveyor where the analytical predictions correlate closely to the measured results.